A study of Philippine hand embroidery with focus on the Lumban, Laguna industry. - Panganiban, Nicole Odette Lavilles; Dizon, Angelita M. (1993.)
This study entitled A STUDY OF PHILIPPINE HAND EMBROIDERY WITH FOCUS ON THE LUMBAN, LAGUNA INDUSTRY provides relevant information about the said industry specifically covering the aspects or organization, finance, production and marketing. Data were gathered through interviews with embroidery producers and embroidery workers in Lumban. Lumban boasts of hand embroidery as its foremost cottage industry and in this study, this problems and potentials were explored.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Embroidery--Philippines--Laguna.